International Boundaries and Borderlands in the Middle East: Balancing Context, Exceptionalism and Representation. Issue 3 (3rd July 2018) - Schofield, Richard
ABSTRACT: Renewed academic interest in the Middle Eastern border is inevitable with the marked increase in fortified territorial limits across the region and the appearance of new borderland spatialities in the sovereign margins of the war-torn Iraqi, Syrian and Yemeni states. If the consequent spectacle of displaced populations confronting state power at the international boundary seems a defining image, this article concentrates on two other dominant, less publicised but still relevant border representations from the recent past: territorial definition and its deterministic association with conflict in the northern Gulf and the resource-driven finalisation of the peninsula's territorial framework. This follows consideration of the significance of the borderland in the region. The author reflects back here on a long record of research into these issues and argues that all of these contexts must be acknowledged in any balanced appraisal of the Middle Eastern border. The article comments on the challenge of extending regional approaches to the study of borders and – on the centenary of the infamous 1916 Sykes-Picot treaty – acknowledges that the Middle East region's experience of international boundaries continues to be depicted as exceptional. Unsurprisingly, it will conclude that there is no one typical Middle Eastern border.